KEGIATAN MEMBACA SISWA KELAS IV SD SELAMA MASA PANDEMI - Handini, Risa; Handayani, Monika; Kinani, Ristu; Hanafi (VOKAL: Jurnal Ilmiah Bahasa dan Sastra Indonesia, 2024)
This study aims to find out the reading activities by students of SD Negeri Tirtoadi Sleman during distance learning during the COVID-19 pandemic. The specific purpose is to discover the availability of facilities owned by students, the level of parent participation, students' reading activities at school, and their interest in reading. The subject of the study was a grade IV student. This research includes quantitative descriptive research with a survey design. Data collection was conducted using the PIRLS framework questionnaire. Data analysis was conducted using quantitative data analysis. The findings showed that the availability of student facilities in reading activities is still quite good because on average students have facilities for reading activities at home even though students read more in school. The findings from the results of parent participation also prove that 90% of parents actively monitor student learning activities while at home. Most students' reading activities at school focus on spending 1-2 hours in the library, as they prefer learning from teachers' explanations over reading. Despite high interest and motivation in reading due to curiosity, students' reading habits during the pandemic remain similar to their normal learning activities.